Penerapan Big Book Sintaksis Berbasis PBL untuk Meningkatkan Sikap Kritis dan Kemampuan Menulis Kalimat Sederhana Kelas Rendah - Tama, Elvina Prasetia Widya; Purwati, Panca Dewi (YASIN, 2025)
Although writing instruction in elementary education has been the focus of numerous prior studies, research specifically exploring the integration of the Problem-Based Learning (PBL) model with Big Book media to enhance critical attitudes and improve capitalization and punctuation skills among lower-grade students remains limited. This study aims to describe the implementation of the PBL model supported by Big Book media, evaluate its effectiveness in fostering critical thinking, and analyze the improvement in writing skills among second-grade students at SDN Mangkang Wetan 03, Semarang. A mixed-methods approach with an embedded concurrent design was employed, involving 25 students selected through purposive sampling. Data were collected through observation, interviews, documentation, field notes, and written tests (pretest and posttest). Qualitative data were analyzed using the Miles and Huberman model, while quantitative data were processed using N-Gain analysis and descriptive statistics. The results indicate that most students achieved a "Good" category in critical attitude, with an average writing score increase of 22.04 points and an N-Gain score of 0.59, categorized as moderate. The percentage of students achieving learning mastery increased from 68% to 88%. These findings demonstrate that integrating the PBL model with Big Book media effectively enhances students’ active participation and mastery of basic writing conventions. The study concludes that contextual, problem-based instructional approaches supported by concrete visual media are essential for effective language instruction in lower elementary grades. Its implications contribute theoretically to the development of constructivist-based learning and offer practical guidance for teachers in addressing challenges in early writing instruction at the elementary level.